2000
DOI: 10.1029/1999jd900915
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heterogeneous sulphate production in maritime stratiform clouds

Abstract: Abstract. A size-resolved droplet physico chemical model linked to a Lagrangian parcel framework was developed and used to study the heterogeneous sulphate production process in marine stratiform clouds. This model study provides a rigorous approach to cloud chemistry processing by treating the effects of non ideal chemistry on both aqueous phase equilibration and droplet growth using the Pitzer method to overcome many of the shortcomings of alternative thermodynamic methods. In addition, the current study use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…For the sea‐salt‐dominated size fractions (≥2.4 μm), deviations between concentrations and activities at RHs greater than 80% (23 of 32 samples) are generally small [e.g., Chameides and Stelson , 1992] and have only minor influences on estimated pHs (typically <0.2 pH unit [ Keene et al , 2002]). For sea salt at lower RHs and for smaller aerosol size fractions under all conditions, activities and corresponding concentrations for some species (H + and SO 4 2− in particular) diverge substantially [e.g., Kim et al , 1993; Sander and Crutzen , 1996; O'Dowd et al , 2000]. Consequently, our estimates of the ambient pHs for these size fractions and conditions are considered qualitative.…”
Section: Methodsmentioning
confidence: 96%
“…For the sea‐salt‐dominated size fractions (≥2.4 μm), deviations between concentrations and activities at RHs greater than 80% (23 of 32 samples) are generally small [e.g., Chameides and Stelson , 1992] and have only minor influences on estimated pHs (typically <0.2 pH unit [ Keene et al , 2002]). For sea salt at lower RHs and for smaller aerosol size fractions under all conditions, activities and corresponding concentrations for some species (H + and SO 4 2− in particular) diverge substantially [e.g., Kim et al , 1993; Sander and Crutzen , 1996; O'Dowd et al , 2000]. Consequently, our estimates of the ambient pHs for these size fractions and conditions are considered qualitative.…”
Section: Methodsmentioning
confidence: 96%
“…Detailed cloud parcel modelling studies of the heterogeneous oxidation of SO 2 to aerosol sulphate were conducted by O'Dowd et al (2000) both for activated droplets and un-activated haze particles. The simulations showed that dissolved ozone and hydrogen peroxide were the dominant oxidants, with the ozone oxidation pathway dominant on sea salt Gantt et al 2011) activated droplets.…”
Section: Secondary Inorganic Aerosol Formationmentioning
confidence: 99%
“…Two intensive sampling campaigns were designed for the summer (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) March) and winter (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The aim of these field campaigns was to sample atmospheric particulate matter at high flow rates and extended sampling intervals periods (12 to 24 hours) and to subject the samples to an array of analytical techniques to obtain a comprehensive suite of chemical components to better understand of the nature of the impacting sources and transport mechanisms.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of sulphuric acid in aerosol formation in a humid environment has been emphasized in a number of studies. [7,8] It is clear that the understanding of the transformation of sulphur dioxide in the atmosphere is not completely understood. The formation of the dominant atmospheric sulphate compound, ammonium sulphate, poses some interesting questions about the main pathway of SO 2 oxidation in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%